Rituais da dor (uma análise do grupo mães na dor de João Pessoa – PB) - Lima, Anna Georgea Franco Feitosa Mayer de Araújo (2013)
Western societies have experienced a significant increase in urban violence. In Brazilian society, this has been one of the most recurrent topics in the media, the academy, and also as an object of social mobilization. In response to this violence, civil society elaborates mechanisms, the most varied, the resoluteness of their damages and harms, such as training of NGOs, therapeutic groups, and pressure groups, whose goal is to direct government institutions, especially legal the full accomplishment of its objectives. In the city of João Pessoa, Paraíba, there is a group called "Mothers in Pain", formed by mothers, bereaved, who have lost their children because of the violence. They transform their pain, their grief, their longing, fighting for justice and an end to urban violence. What initially draws attention in the study group, is that the pain of those mothers who lost their children is the catalyst for transforming the sense of loss in strength to come out to the streets in demonstrations, calling for Justice and Peace Demonstrations are prepared and articulated in different ways, therefore, talk with the authorities, go to the forum criminal, the Court, to talk about the harsh reality that hit all of them: violence. In their speeches they tell how their lives were marked by violence that befell their children, killing them. This dissertation deals with the relationship between grief, justice, shame, humiliation within the group "Mothers in Pain." It is an ethnographic research that makes use greatly in the field diary and semi-structured interviews. Analyze, among others, the concept of violence and understanding. Violence triggers the loss process. But are the resulting emotions, grief, shame, humiliation, feelings of injustice, which are the lenses through which the existence and practice of group "Mothers in Pain" are read. So, I present here the result of my excursions as a research participant in this group. In this sense, the field of emotions is relevant to point out how important the creation of social ties and networks of solidarity between mothers who share the same pain and have also affected me while, researcher, mother and actress social.